Interaction of human thyroid hormone receptor beta with transcription factor TFIIB may mediate target gene derepression and activation by thyroid hormone. - Baniahmad, A (1993)
The human thyroid hormone receptor beta (hTR beta) is capable of both transcriptional silencing and hormone-dependent activation. However, the detailed mechanism of this transcriptional regulation remains to be elucidated. One possibility is that hTR beta interacts directly with factors of the basal transcriptional machinery, thereby modulating basal promoter activity in a direct manner, as has been shown for other transcription factors. Here, we show that hTR beta interacts specifically with the human basal transcription factor TFIIB. Deletion analysis revealed two contact sites in the receptor: one is located in the N terminus, while the other is part of the ligand-binding domain (LBD) and is located at the C terminus. Interestingly, each receptor contact site interacts with different sites in TFIIB. Cotransfection experiments revealed that, when fused to the DNA-binding domain of yeast transcription factor GAL4, the C-terminal interaction site of hTR beta was transcriptionally inactive; however, when it was cotransfected with the remaining part of the LBD on a separate molecule, silencing function was restored. In agreement with that, we show that thyroid hormone is able to significantly decrease the interaction of its receptor LBD with TFIIB. Our data suggest that hTR beta acts as a transcriptional silencer by interacting with TFIIB and that thyroid hormone may act in part by preventing transcriptional repression at this level.